Dynamic regulation of Emi2 by Emi2-Bound Cdk1/Plk1/CK1 and PP2A-B56 in meiotic arrest of xenopus eggs - Isoda, Michitaka; Inoue, Daigo (Developmental cell, 2011)
Summary: In vertebrates, unfertilized eggs are arrested at metaphase of meiosis II by Mos and Emi2, an inhibitor of the APC/C ubiquitin ligase. In Xenopus, Cdk1 phosphorylates Emi2 and both destabilizes and inactivates it, whereas Mos recruits PP2A phosphatase to antagonize the Cdk1 phosphorylation. However, how Cdk1 phosphorylation inhibits Emi2 is largely unknown. Here we show that multiple N-terminal Cdk1 phosphorylation motifs bind cyclin B1-Cdk1 itself, Plk1, and CK1δ/ε to inhibit Emi2. Plk1, after rebinding to other sites by self-priming phosphorylation, partially destabilizes Emi2. Cdk1 and CK1δ/ε sequentially phosphorylate the C-terminal APC/C-docking site, thereby cooperatively inhibiting Emi2 from binding the APC/C. In the presence of Mos, however, PP2A-B56β/ε bind to Emi2 and keep dephosphorylating it, particularly at the APC/C-docking site. Thus, Emi2 stability and activity are dynamically regulated by Emi2-bound multiple kinases and PP2A phosphatase. Our data also suggest a general role for Cdk1 substrate phosphorylation motifs in M phase regulation.